2010
DOI: 10.1039/b919475d
|View full text |Cite
|
Sign up to set email alerts
|

High throughput assembly of spatially controlled 3D cell clusters on a micro/nanoplatform

Abstract: Guided assembly of microscale tissue subunits (i.e. 3D cell clusters/aggregates) has found applications in cell therapy/tissue engineering, cell and developmental biology, and drug discovery. As cluster size and geometry are known to influence cellular responses, the ability to spatially control cluster formation in a high throughput manner could be advantageous for many biomedical applications. In this work, a micro- and nanofabricated platform was developed for this purpose, consisting of a soft-lithographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 46 publications
1
46
0
Order By: Relevance
“…[24][25][26][27][28][29][30][31][32] For example, microwell systems have been utilized for ES cell studies to control the formation of ES cellular aggregates because the size of aggregates regulates ES cellular differentiation. [33][34][35] Here, we present a simple and rapid cell patterning method to provide versatile control over the geometry of cellular niches formed using readily available Transwells.…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32] For example, microwell systems have been utilized for ES cell studies to control the formation of ES cellular aggregates because the size of aggregates regulates ES cellular differentiation. [33][34][35] Here, we present a simple and rapid cell patterning method to provide versatile control over the geometry of cellular niches formed using readily available Transwells.…”
Section: Resultsmentioning
confidence: 99%
“…This study indicated that the resistance of drug adsorption could only be obtained by simultaneously increasing hydrophobicity and reducing electrostatic interaction. It is quite different from the protein resistance via simply utilizing the hydrophilic interaction [5,20,21]. The hydrophilic PEO modification successfully reduced protein adsorption to less than 10% of that on unmodified surfaces [5,20] but only had a little effect on reducing base drug adsorption.…”
Section: Membranementioning
confidence: 97%
“…It is quite different from the protein resistance via simply utilizing the hydrophilic interaction [5,20,21]. The hydrophilic PEO modification successfully reduced protein adsorption to less than 10% of that on unmodified surfaces [5,20] but only had a little effect on reducing base drug adsorption. Reducing the drug adsorption is more difficult than protein adsorption, because most of the drugs are positively charged which readily adsorb onto negatively charged synthetic polymers [2][3][4] while the proteins are mostly negatively charged at pH 7.4 that could avoid this problem [22].…”
Section: Membranementioning
confidence: 97%
“…4,5 Constraining cell movement is necessary for atomic force microscopy 6 or to study the formation of cell clusters. 7,8 Lecault and colleagues 9 employed 160 lm cubic microchambers to study clonal culture of primitive mouse hematopoietic stem cells using live-cell imaging. 9 Development of microdevices for long-term perfusion culture is a significant bioengineering challenge requiring in-depth analysis and optimisation of system properties.…”
mentioning
confidence: 99%